1979
DOI: 10.3109/01485017908988408
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Leydig Cell Responsiveness to LH/hCG in the Rat

Abstract: The effects of prolactin and 2-bromo-a-ergocryptine (CB-154) on Leydig cell function in intact and hypophysectomized male rats were studied. The conclusions can be summarized as follows:prolactin (1) has a direct stimulatory effect on the number of LH receptors on rat Leydig cells, (2) has no effect on the characteristics of the dose-response curve of isolated Leydig cells (hCG stimulated androgen production) in vitro even after treatment with pharmacological doses in vivo, and (3) acts synergistically with LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…11). Both forms of PRL increased expression of the LHR, a result consistent with positive effects of PRL administration in prepubescent and hypophysectomized animals (2,10,32,36,54) because this would be expected to increase sensitivity to LH. Making the assumption that the mRNA was translated into protein displayed on the plasma membrane, one might also have expected this to normalize 3␤-HSD by increasing sensitivity to LH when LH levels were normal in the adult animals, but this was not the case in the presence of either form of PRL.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…11). Both forms of PRL increased expression of the LHR, a result consistent with positive effects of PRL administration in prepubescent and hypophysectomized animals (2,10,32,36,54) because this would be expected to increase sensitivity to LH. Making the assumption that the mRNA was translated into protein displayed on the plasma membrane, one might also have expected this to normalize 3␤-HSD by increasing sensitivity to LH when LH levels were normal in the adult animals, but this was not the case in the presence of either form of PRL.…”
Section: Discussionsupporting
confidence: 53%
“…In studies by other investigators, PRL has been shown to be responsible for the induction of Leydig cell proliferation and differentiation in prepubertal hypophysectomized rats (10) and the maintenance of Leydig cell morphology, upregulation of luteinizing hormone receptor (LHR) expression, and potentiation of luteinizing hormone (LH)-induced steroidogenesis in hypophysectomized rats (2,10,32,36,54). In vitro approaches, utilizing murine Leydig tumor cell lines and isolated rodent primary Leydig cell cultures, have concluded that PRL exerts trophic effects on Leydig cell steroidogenic function, mostly through an effect on LH-induced testosterone production (23,32,33,45), although some of these effects have been shown to have biphasic dose-response curves, with high concentrations actually exerting an inhibitory effect (33).…”
mentioning
confidence: 99%
“…In the rat, Belanger et al [4] showed that PRL treatment increased serum and testicular androgen levels as early as 2 h after injection. In vivo treatment with PRL stimulates in vitro androgen production by testicular interstitial cells [23]. Mild chronic hyperprolactinaemia also results in an increase in serum LH levels [2] as well as in testicular LH receptors [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies generally suggest that PRL positively modulates testicular functions in several ways, as follows: PRL is involved in the upregulation of LH receptor on Leydig cells [2,3], in the increase in FSH receptors in Sertoli cells [4], and in the meiosis of germ cells [5]. In contrast, none of the parameters or functions of the male reproductive organs are affected in PRL knockout (KO) or PRL receptor (PRLR) KO mice [6,7].…”
mentioning
confidence: 99%
“…Dev. 56: [567][568][569][570][571][572][573][574] 2010) he various functions of prolactin (PRL) in vertebrates include the growth and differentiation of the mammary epithelium, lactation in mammals, osmoregulation and parental behavior in teleosts, amphibian development, broodiness in hens, crop sac production in pigeons and immunoregulation [1].Moreover, many studies generally suggest that PRL positively modulates testicular functions in several ways, as follows: PRL is involved in the upregulation of LH receptor on Leydig cells [2,3], in the increase in FSH receptors in Sertoli cells [4], and in the meiosis of germ cells [5]. In contrast, none of the parameters or functions of the male reproductive organs are affected in PRL knockout (KO) or PRL receptor (PRLR) KO mice [6,7].…”
mentioning
confidence: 99%